DNA and BSA binding and cytotoxic properties of copper(II) and iron(III) complexes with arylhydrazone of ethyl 2-cyanoacetate or formazan ligands - Martins, Nuno (2017)
Several known water soluble [Cu(1N,O2:2O-HL1)(S)]2 [S = CH3OH (1), (CH3)2NCHO (2)] and [Cu(N-HL1)(en)2]∙CH3OH∙H2O (3) CuII complexes were prepared by reaction of CuII nitrate hydrate with the new (E/Z)-4-(2-(1-cyano-2-ethoxy-2-oxoethylidene)hydrazinyl)-3-hydroxybenzoic acid (H3L1), in the presence (for 3) or absence (for 1 and 2) of ethylenediamine (en), while the FeIII complex [Fe(N3-HL2)2] (4) was synthesized by treatment of iron(III) chloride hexahydrate with the new (1E,1E)-N',2-di(1H-1,2,4-triazol-3-yl)diazenecarbohydrazonoyl cyanide (H3L2). The interaction of calf thymus DNA (CT DNA) and bovine serum albumin (BSA protein) with complexes 1−4 has been investigated by absorption and fluorescence titration methods. The observed DNA binding constants, number of DNA binding sites (s ≤ 1) for complexes and viscosity data suggest that the intercalative mode of binding to CT DNA. All the complexes show good binding propensity to the BSA, giving KBSA values of 0.97(±0.10) × 106 (1), 1.19(±0.09) × 106 (2), 0.50(±0.01) × 106 (3) and 1.06(±0.08) × 106 M-1 (4). The in vitro anti-proliferative study establishes the anticancer potency of complexes 1−4 and cisplatin against the human cervical (HeLa) and breast (MCF7) cancer cell lines; noncancer breast epithelial (MCF10) cells were also investigated. The observed IC50 values of the complexes 1 (8.3, 11.9 and 44.8 μM), 2 (7.0, 7.1 and 35.6 μM), 3 (18.1, 20.4 and 58.8 μM), 4 (13.2, 15.1 and 79.4 μM) and cisplatin (4.02, 3.42 and 89.5 μM) against the HeLa, MCF7 and MCF-10a cells, respectively, suggest that 2 can be explored further as a potential anticancer drug.